2018
DOI: 10.1146/annurev-polisci-050517-120425
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomy of Protest Voting

Abstract: Observers of elections often report that voters have engaged in protest voting. We find that “protest voting” refers to a wide range of behaviors, and we create a taxonomy of these phenomena. Support for fringe or insurgent parties is often labeled as protest voting. Voting theorists have used the term in a completely different way, identifying an unusual type of tactical voting as protest voting. Protest voting also occurs when voters cast blank, null, or spoiled ballots. There are also instances when protest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 40 publications
(39 reference statements)
1
35
0
2
Order By: Relevance
“…403-418. 19 McMurray, 2017 Véanse, con referencias adicionales, Álvarez;Kiewiet;Núñez, 2018, p. 2;Superti, 2015, p. 4;Zufilkarpasic, 2001, pp. 253 y 264-266.…”
Section: Motivaciones Subyacentes Al Voto En Blancounclassified
“…403-418. 19 McMurray, 2017 Véanse, con referencias adicionales, Álvarez;Kiewiet;Núñez, 2018, p. 2;Superti, 2015, p. 4;Zufilkarpasic, 2001, pp. 253 y 264-266.…”
Section: Motivaciones Subyacentes Al Voto En Blancounclassified
“…However, if distrust extends to the basic rules of democracy itself, there is less reason to vote since citizens no longer assume that their vote will make a difference. Especially with regard to the electoral process itself, Alvarez et al (2018) have demonstrated that citizens are less motivated to vote if they do not believe the electoral procedure will be administered in a fair manner. While it might be true that political distrust will be associated with various non-institutionalized forms of political participation, it is most likely to deter electoral participation."…”
Section: )mentioning
confidence: 99%
“…Ο τέταρτος παράγοντας (με ιδιοτιμή 1.15, 8% της διακύμανσης, και όλα τα φορτία > .9) ονομάστηκε εξτρεμισμός (συμμετοχή σε βανδαλισμούς και βίαιες συγκρούσεις, Pearson's r= .89). Η παρούσα έρευνα δεν εξετάζει την εκλογική συμπεριφορά, η οποία έχει ερευνηθεί ως η συνήθης πολιτική συμπεριφορά (βλ., Alvarez, Kiewiet, & Núñez, 2018. Obschonka, Stuetzer, Rentfrow, Lee, Potter, & Gosling, 2018, αλλά τις πολιτικές συμπεριφορές που εκδηλώθηκαν ως απάντηση στην τρέχουσα πολιτική πραγματικότητα της συζήτησης των μνημονίων.…”
Section: ερωτηματολόγιοunclassified